1988
DOI: 10.1007/bf00910497
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in children of parents with recurrent depression

Abstract: We examined the prevalence of psychopathology in children of parents with recurrent major depression (n = 61) and children of normal control parents (n = 46). Rates of psychopathology in the children of depressed parents were consistently higher when compared either with the control children or with rates of disorder reported for nonclinically referred children from other studies. Forty-one percent of high-risk children met criteria for at least one psychiatric disorder compared with 15% of low-risk children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
1
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(115 citation statements)
references
References 30 publications
6
104
1
4
Order By: Relevance
“…Orvaschel and colleagues (35) report increased psychological disturbance in children of depressed parents, and Downey and Coyne (16) report a sixfold increased risk of depression in offspring of depressed parents versus control children. Binge eating was the other specific maternal psychopathology to correlate with child behavioral problems, again in sample 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orvaschel and colleagues (35) report increased psychological disturbance in children of depressed parents, and Downey and Coyne (16) report a sixfold increased risk of depression in offspring of depressed parents versus control children. Binge eating was the other specific maternal psychopathology to correlate with child behavioral problems, again in sample 2.…”
Section: Discussionmentioning
confidence: 99%
“…4 No.1 Jan. 1996 shown to have numerous ramifications on child development (35,40). Assessment of eating disorders was conducted because many of the mothers were themselves seeking treatment for obesity, and the prevalence of maladaptive eating such as binge eating has been reported as relatively high (30%) in treatment seeking obese adults (43).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that, even with the effects of chronic stress statistically controlled, there were still differences in the psychosocial outcome variables among groups, and there was particular impairment in children of unipolar mothers (30). Other studies (31)(32)(33)(34), in which there were no demographic differences (age, marital status and socioeconomic level) between depressed and nondepressed parents, have confirmed an increased risk of psychopathology in the children of depressed parents. It seems that onset of a major depression disorder before 30 years of age in parents increases the risk of their children developing depression quite early during childhood (33,34).…”
Section: Cognitive Developmentmentioning
confidence: 96%
“…Infants aged as young as 3 months have been shown to ably detect their mother's mood and to modify their own responses accordingly (10). While cognitive skills (11), expressive language development (12), and attention (13) have been negatively influenced by PPD, it has also been reported that children of mothers with depression are 2 to 5 times more likely to develop long-term behavioural problems (14,15). Child neglect and (or) abuse (16) and marital stress resulting in separation or divorce (17,18) are other reported outcomes.…”
mentioning
confidence: 99%